Corn Yield Response to Sulfur Applied with Nitrogen Fertilizer - T. E. Husa; D. A. Ruiz Diaz (Kansas Agricultural Experiment Station Research Reports, 2021)
The objective of this study was to evaluate the effect of nitrogen (N) with added sulfur (S) fertilizer on corn yield. The treatments included 1) a control with no sulfur and no nitrogen; 2) urea ammonium nitrate (UAN) (180 lb N/a; 0 lb S/a); and 3) UAN plus ammonium thiosulfate (ATS) (180 lb N/a; 15 lb S/a). Both the UAN and UAN+ATS were balanced to 180 lb N/a. These three treatments were evaluated at two locations in 2019 and three locations in 2020. Preliminary results show that yield trended upward with the application of nitrogen plus sulfur fertilization over N alone, and the potential response to S was affected by soil characteristics and S supply from irrigation water.
Keywords: sulfur; nitrogen; corn